Angry Ginger : Power Training Day - Kowalik, Melissa, 1988- ([Coolalinga, Northern Territory] : Cow Lick Publishing, 2021)
It's Power Training Day with the power teacher, Mr Creature. Join the Mars protector team and watch Angry Ginger blow off some steam, whilst the Dark Rebel Thorn reveals a new evil scheme.
For children.
Keywords: Redheads -- Juvenile fiction; Children's stories; Adventure fiction; Australian